PERANAN BADAN KEHORMATAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA PEKANBARU TAHUN 2016-2019 - Putri Diana Fitri; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The significance of the existence of this BK was originally to answer the needs of the current reforms that demand changes. The existence of this institution is very important and strategic in carrying out its duties and functions in order to realize a clean government. Many members of the council after being elected to the legislature work arbitrarily without anyone else caring, let alone supervising them, for example, rarely serve as members of the Council and rarely attend hearings or meetings, even though the issues discussed in those meetings are related to the interests of their constituents. which in this case is the people. In addition, in optimizing the implementation of the duties and functions of the DPRD, many council members (DPRD) after being elected as members of the legislature often fail to carry out their duties. The purpose of this study was to determine and analyze the role of the Honorary Board of the Pekanbaru City Regional House of Representatives in 2016-2019. The research method used in this study is a qualitative method. This type of research is descriptive. This research was conducted in Pekanbaru City. The role of the Honorary Board for members of the Pekanbaru City Regional House of Representatives 2016-2019. The results of this study are the role of the Honorary Board of the Regional People's Representative Council of Pekanbaru City in 2016-2019. The Honorary Board of the Pekanbaru City DPRD in 2016-2019 has handled (6) six cases of violations of DPRD rules and regulations by members of the Pekanbaru City DPRD, all of these cases have been handled by the Honorary Board in accordance with applicable regulations. Supporting and Inhibiting Factors for the Role of the Honorary Board of the Pekanbaru City Regional House of Representatives 2016-2019. There are 5 (five) internal factors that hinder the implementation of the duties of the Honorary Board of the Pekanbaru City DPRD. There are two external factors that become obstacles faced by the Honorary Board of the Pekanbaru City Regional People's Representative Council. The conclusion of this research is the implementation of the role of the Honorary Board of the Pekanbaru City Regional House of Representatives in 2016-2019. Keywords: Role, Honorary Body, People's Representative Council.